2005
DOI: 10.1002/ajh.20470
|View full text |Cite
|
Sign up to set email alerts
|

von Willebrand disease R1374C: Type 2A or 2M? A challenge to the revised classification. High frequency in the northwest of Spain (Galicia)

Abstract: Patients initially diagnosed with type 1 von Willebrand disease (VWD) have been reclassified as type 2 after a more exhaustive analysis in several studies. Our study's objectives were (1) to reanalyze patients that were previously diagnosed as type 1 to achieve a more accurate diagnosis and (2) to compare the von Willebrand factor (VWF) ristocetin cofactor assay (VWF:RCo) and the VWF collagen binding assay (VWF:CB) in order to evaluate the possibility of replacing the former assay with the latter in the diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 17 publications
7
49
0
Order By: Relevance
“…Patients analyzed by others with mutations such as R1205H, R1315C, and R1374C have previously been described as having Vicenza subtype or type 2M VWD. [26][27][28] The 95% mutation detection sensitivity in group 1 (at least 1 mutation identified in 54 of 57 ICs) indicated that the combination For personal use only. on May 10, 2018. by guest www.bloodjournal.org From of mutation detection techniques used in the study detected most exonic and closely flanking intronic mutations.…”
Section: Org Frommentioning
confidence: 99%
“…Patients analyzed by others with mutations such as R1205H, R1315C, and R1374C have previously been described as having Vicenza subtype or type 2M VWD. [26][27][28] The 95% mutation detection sensitivity in group 1 (at least 1 mutation identified in 54 of 57 ICs) indicated that the combination For personal use only. on May 10, 2018. by guest www.bloodjournal.org From of mutation detection techniques used in the study detected most exonic and closely flanking intronic mutations.…”
Section: Org Frommentioning
confidence: 99%
“…Other investigators preferred to classify it as type 2A due to the lower relative proportion of HMWM [7]. It has also been categorized as severe type 1 VWD [8], as well as type 1B [9], and 1B variant of 2A [10]. Finally, in the ISTH registry of VWD [11], it has been included as unclassified VWD.…”
Section: Introductionmentioning
confidence: 99%
“…However, the VWF:CB assay is unable to discriminate defective platelet-binding VWD variants with normal multimeric patterns such as VWD type 2M [19]. Moreover, it has been observed that the results for VWF:CB are dependent on the type of collagen used [10]. The VWF:CB/VWF:Ag ratio was indeed found to be higher (0.7) for type I collagen, while the results for type III collagen were variable [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations